Eusyllinae, Exogoninae and Autolytinae (Syllidae: Polychaeta) from the Southern Mexican Pacific, with the description of three new species - Salcedo, Diana L. O.; Martín, Guillermo San; Solís-Weiss, Vivianne (Zootaxa, 2016)
Previous studies have dealt recently with syllid polychaetes in soft sediments from Acapulco Bay (Southern Mexican Pacific) with new species and new records of the subfamily Syllinae published, but the remaining subfamilies found in the area had not been included. This study deals with syllids belonging to those subfamilies: Eusyllinae, Exogoninae and Autolytinae, since the Anoplosyllinae were not found. Three species are described as new: Odontosyllis septemdentata n. sp., characterized by having bidentate falcigers and a trepan with 7 teeth alternating in size; Sphaerosyllis tetralobata n. sp., which is characterized by having unidentate compound chaetae and segments divided in four annuli, and Prosphaerosyllis sotoi n. sp., characterized by having compound chaetae with short and hooked unidentate blades, and by being the only species of the genus that lacks dorsal cirri in the second parapodia. Additionally, Westheidesyllis gesae (Perkins 1981) is newly recorded for the Pacific Ocean, while Odontosyllis fulgurans (Audouin & Milne Edwards 1834), Erinaceusyllis bidentata (Hartmann-Schröder 1974) and Myrianida dentalia (Imajima 1966) are recorded for the first time from the Mexican Pacific coasts.